Correction: Genus-wide Leptospira core genome multilocus sequence typing for strain taxonomy and global surveillance. - Julien Guglielmini; Pascale Bourhy; Olivier Schiettekatte; Farida Zinini; Sylvain Brisse; Mathieu Picardeau (Public Library of Science (PLoS), 2020)
[This corrects the article DOI: 10.1371/journal.pntd.0007374.].